Transparent TiO2 thin films with high photocatalytic activity for indoor air purification. Issue 55 (12th December 2022) - Sydorenko, Jekaterina; Mere, Arvo; Krunks, Malle; Krichevskaya, Marina; Acik, Ilona Oja
Abstract : Enhanced photocatalytic oxidation of indoor VOC mixtures on transparent polycrystalline spray-deposited TiO2 thin films under ultraviolet and visible light. Abstract : The development of low-material-quantity, transparent, anatase TiO2 nanoparticle free thin films as photocatalytic materials together with a profound understanding of their photocatalytic activity under ultraviolet (UV-A) and visible (VIS) light is crucial for environmentally friendly indoor air photocatalytic coatings. In this work, a TiO2 thin film modified by an increased amount of acetylacetone in the precursor solution with a material quantity of 0.2 mg cm −2 was successfully deposited on a borosilicate glass substrate by ultrasonic spray pyrolysis. VOC degradation as a single model pollutant and in mixtures under different operating conditions was studied in a multi-section continuous flow reactor. Under UV-A the reaction rate constants for heptane and toluene oxidation as individual pollutants were 1.7 and 0.9 ppm s −1, respectively. In 9 ppm VOC mixtures of acetaldehyde, acetone, heptane and toluene all the compounds were completely oxidized in a reaction time of less than 50 s. The TiO2 film showed moderately high photocatalytic activity under VIS light. The conversions of acetaldehyde, acetone, heptane and toluene in 9 ppm VOC mixtures under VIS light reached 100, 100, 78 and 31%, respectively. The synthesized TiO2 film shows promising ability in indoor air purification from VOCs. The results of this study give an extensive estimation of the thin film's photocatalytic efficiency and provide valuable data for future applications in environmental remediation.